The Difference of Perceived HIV Stigma between People Living with HIV Infection and Their Families - Ibrahim, Kusman; Kombong, Rita; Sriati, Aat (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: The stigma of HIV and AIDS become a significant barrier to prevention, treatment, and care for HIV infected people. Disclosure of HIV status to the family can help People Living with HIV infection (PLWH) to obtain support and comfort from their family. However, the difference of perceived HIV stigma held by patients and families has become problematic and lead to inadequate responses of PLWH and their families.Purpose: This study aimed to examine the difference in perceived HIV stigma between PLWH and their families.Methods: This was a cross-sectional study involving 60 respondents that consisted of 30 PLWH and 30 family members. They were recruited purposively in an HIV clinic of a residencial hospital in West Java Province, Indonesia. The perceived HIV stigma was measured by the Berger’s HIV stigma scale (BHSS), and the Liu’s Courtesy Stigma Scale (LCSS) was used to measure the perceived HIV stigma at the family level. Data were analyzed using descriptive and inferential analysis (independent t-test) to test the difference in perceived HIV stigma between PLWH and their families.Results: The study found that most PLWH and their families perceived HIV stigma at a moderate level (70% vs. 63.4%, respectively). There was a significant difference in perceived HIV stigma between PLWH and their families (t=3.4; p=0.001). The PLWH perceived HIV stigma was higher than their family members (M=41, SD=13.9 vs. M=28.5, SD=14.0).Conclusion: This study highlighted that PLWH and their family have different perceptions regarding HIV stigma, which can lead to different responses. Therefore, nurses and other health care providers need to be aware and take a comprehensive assessment-related perceived HIV stigma in order to provide a high quality of nursing care, mainly dealing with HIV stigma for both PLWH and their family members.